Trayectorias contemporáneas del miedo en América Latina - David Barrios Rodríguez (Les Cahiers ALHIM)
At the beggining of XXI century, collective fears have dramatically transformed in Latin America. Although this modification is general, it carries specific expressions in each context and Latin America combines a remarkable mixture between changes in the subjective perception of the dangers, as well as in their concrete forms of expression. The exceptional centrality acquired by the speech on security in Latin America can be observed. As a correlate to this process, we witness the gradual alteration in the dynamics of production and trafficking of narcotic drugs throughout the continent, which has involved the opening of a period of violence unprecedented by virtue of its size, forms of expression, as well as the social repercussions that it entails.